Designing Environment-Based Interactive Multimedia for Enhanced Language Learning in Indonesian Language and Literature Education Program - Sitti Harisah; Ida Nur'aeni; Ulinsa Ulinsa; Asrianti Asrianti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Traditional teaching methods in the "Learning Models" course of the Indonesian Language and Literature Education program often lack engagement and contextual relevance. This study aims to develop and assess the feasibility of environment-based interactive multimedia as an innovative instructional tool to improve comprehension and application among prospective teacher candidates. This research employed a developmental approach, incorporating data from observations, interviews, and questionnaires. A product assessment questionnaire served as the primary instrument. Feasibility was evaluated through expert validation and user testing, including individual and small group trials. Both qualitative and quantitative descriptive analyses were used to interpret the data. The developed multimedia product demonstrated high feasibility scores: content expert validation (91.5%), instructional design expert validation (91.5%), media expert validation (94.0%), individual trial (94.7%), and small group trial (88.2%). All results fall within the "very good" or "good" categories, indicating strong validity and practicality. Findings suggest that environment-based interactive multimedia enhances learner engagement and supports effective instruction in teacher education. The product is well-suited for integration into the "Learning Models" course. The multimedia product is highly feasible for educational implementation. Further research is recommended to examine its effectiveness across other courses and learner populations.